Impact of CPOE on Mortality Rates – Contradictory Findings, Important Messages - Ammenwerth, E.; Talmon, J.; Ash, J. S.; Bates, D. W.; Beuscart-Zéphir, M.-C.; Duhamel, A.; Elkin, P. L.; Gardner, R. M.; Geissbuhler, A. (Methods of Information in Medicine, 2006)
Objective: To analyze the seemingly contradictory results of the Han study (Pediatrics 2005) and the Del Beccaro study (Pediatrics 2006), both analyzing the effect of CPOE systems on mortality rates in pediatric intensive care settings.Methods: Seven CPOE system experts from the United States and Europe comment on these papers.Results: The two studies are not contradictory, but almost non-comparable due to differences in design and implementation. They demonstrate the range of outcomes that can be obtained from introducing informatics applications in complex health care settings. Implementing informatics applications is a socio-technical activity, which often depends more on the organizational context than on a specific technology. As health informaticians, we must not only learn from failures, but also avoid both uncritical scepticism that may arise from drawing overly general conclusions from one negative trial, as much as uncritical optimism from limited successful ones.Conclusion: The commentaries emphasize the need to promote systematic studies for assessing the socio-technical factors that influence the introduction of increasingly sophisticated informatics applications within complex organizations. The emergence of evidence-based health informatics will be based both on evaluation guidelines and implementation guidelines, both of which increase the chances of successful implementation. In addition, well-educated health informaticians are needed to manage and guide the implementation processes.
Keywords: Evaluation studies; CPOE; evidence-based health informatics; mortality